Go to the river: Understanding and experiencing the Liard watershed. - Staveley, Jeremy (Author); Smith, Angèle (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2013)
This study contributes to an emerging space of interdisciplinary literature that explores the cultural dynamics people and rivers and the associated contestations. A network of rivers in northern British Columbia, all within the Liard River watershed, provides a relevant case study to examine such topics. Data and analysis are presented using a phenomenological approach that employs archival and participatory fieldwork. Through this research, I ask: why do people go to the river ? In attempting to understand the significance of rivers in people's lives, Go to the River addresses questions concerning the Liard watershed, including: how interpretations of rivers are represented in historic maps the significant transitions during the nineteenth and twentieth century that redefined human-river relations and how rivers are still experienced through direct lived engagements. I argue that past and present direct experiences with rivers are essential in reframing the dialogue about the future of rivers in western Canada. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1805847